2022
DOI: 10.1002/ehf2.13883
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels and prognostic cut‐offs of sST2, hs‐cTnT, and NT‐proBNP in women vs. men with chronic heart failure

Abstract: AimsTo define plasma concentrations, determinants, and optimal prognostic cut-offs of soluble suppression of tumorigenesis-2 (sST2), high-sensitivity cardiac troponin T (hs-cTnT), and N-terminal pro-B-type natriuretic peptide (NT-proBNP) in women and men with chronic heart failure (HF). Methods and resultsIndividual data of patients from the Biomarkers In Heart Failure Outpatient Study (BIOS) Consortium with sST2, hs-cTnT, and NT-proBNP measured were analysed. The primary endpoint was a composite of 1 year car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 56 publications
(177 reference statements)
0
12
0
Order By: Relevance
“…These data indicate the importance of analyzing sST2 and other HF biomarkers according to sex. Recent studies have demonstrated that sST2 and other HF biomarkers like high sensitivity cardiac troponin T (hs-cTnT) differ by sex and that sex-specific cutoffs are needed to enhance determination of risk for hospitalization or death from HF ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data indicate the importance of analyzing sST2 and other HF biomarkers according to sex. Recent studies have demonstrated that sST2 and other HF biomarkers like high sensitivity cardiac troponin T (hs-cTnT) differ by sex and that sex-specific cutoffs are needed to enhance determination of risk for hospitalization or death from HF ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients were classified as having HFrEF (LVEF ≤ 40%), HF with mildly reduced LVEF (HFmrEF, LVEF 41–49%) or HFpEF (LVEF ≥ 50%) according to the European Society of Cardiology (ESC) guidelines ( 18 , 19 ). In 4,540 patients with chronic HF, they found that HFrEF was more prevalent in men (88% vs. 73%, p < 0.001), while HFmrEF and HFpEF occurred more often in women (10% vs. 7% and 17% vs. 5%; both p < 0.001), and men had significantly higher serum levels of sST2 and high sensitivity cardiac troponin T than women but there were no sex differences in NT-proBNP ( 17 ). Another large study by Suthahar et al examined sex differences in primary CVD biomarkers including sST2 from several large cohorts and reported that sST2 was elevated in the sera of men with chronic HF and that there was an interaction between sex and age ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Troponin augmentation among patients hospitalized with COVID-19 was associated with a higher risk of death [ 48 ]. Concerns related to the increased level of natriuretic peptides suggest its non-specificity, while the reported pulmonary embolism events should only be included in the appropriate clinical context [ 102 , 103 , 104 ].…”
Section: Cardiac Thrombotic Complicationmentioning
confidence: 99%
“…These facts lead us to consider whether thorough monitoring of the serum concentrations of hs-cTn should be incorporated in routine optimal guidebased management (OGBM) of HF, whereas peak concentrations of hs-cTn retain their discriminative potency in acute and chronic HF. Data from HF patients included in the Biomarkers in Heart Failure Outpatient Study (BIOS) Consortium showed a significant difference in prognostic cut-offs of hs-cTnT between male and female patients with HF, whereas there was no difference with respect to NT-proBNP concentrations [49].…”
Section: Extracellular Fibrosis and Inflammationmentioning
confidence: 99%